Revised generic placement of Bruchomorpha rugosa Metcalf (Hemiptera: Fulgoroidea: Caliscelidae) with an assessment of Fitchiella Van Duzee, a genus of conservation interest - Hendrix, Solomon V.; Bartlett, Charles R.; Freitas, Abner S. De (Zootaxa, 2025)
The piglet bug Bruchomorpha rugosa is transferred to the genus Fitchiella, as Fitchiella rugosa (Metcalf, 1923) comb. nov., based on morphological review. The composition of the genus Fitchiella is preliminarily assessed, illustrated, and divided into two morphological species groups. A taxonomic revision is needed to clarify the diagnostic features of some species. The need for further conservation assessments of prairie-endemic true hoppers and the importance of stabilizing taxonomic nomenclature for groups of conservation concern are briefly discussed.